Psoriasis - Khakima Khusnitdinova; Dilshod Khakimov; Bekzoda Askarova (Genius Journals, 2022)
The purpose of the article is to review the most common disease- psoriasis.
Keywords: Psoriasis; psoriasis classification; PUVA therapy; dermatology